The Pattern of Breastfeeding and Providing Supplement Increase Nutritional Status For 7–24 Month Children - Esti Yunitasari; Hesti Permanasari; Retnayu Pradanie (Universitas Airlangga, 2010)
Introduction: Infants grow and develop rapidly therefore they tend to suffer from malnutrition when they couldn’t get adequate nutrition. The infant nutrient status is influenced by many factors such as the breastfeeding pattern and the providing supplement meal pattern. The purpose of this study was to analyze correlation between breastfeeding and providing supplement with 7–24 month child nutritional status.Methods: This study used cross sectional design. Population was mothers who were breastfeeding and providing supplemental meal to their infants age 7 to12 months at Nuri Posyandu, in Kademangan Puskesmas. Samples consisted of 16 mothers with their infants, enrolled based on inclusion criteria. The independent variables were breastfeeding pattern and providing supplement meal pattern. The dependent variable was the nutritional status of the infant age 7 to 12 month. Data were collected by questionnaire and the infant weight was interpreted using Road to Health Card (KMS) then analyzed by spearman’s rank test with significance level ofα ≤ 0.05.Results: Result showed a strong correlation between breastfeeding pattern and nutritional status of the infant age 7 to 12 months (p = 0.001) and adequate correlation was also found between the providing supplement meal pattern and the nutritional status of the infant of 7 to 12 months (p = 0.036).Conclusion: In conclusion, both of breastfeeding and providing supplement meal correctly have correlation to the good infant nutritional status. Further studies should use other designs that enable data to be collected more than once to obtain better reliability in accuracy.The Pattern of Breastfeeding and Providing Supplement Increase Nutritional Status For 7–24 Month Children